Assessing the effect of anesthetic gas mixtures on hyperpolarized 13C pyruvate metabolism in the rat brain - Healicon, R; Rooney, C; Ball, V; Shinozaki, A; Miller, J; Smart, S; Radford-Smith, D; Anthony, D; Tyler, D; Grist, J (Wiley, 2022)
Purpose To determine the effect of altering anesthetic oxygen protocols on measurements of cerebral perfusion and metabolism in the rodent brain.